Sports Economics : Understanding the Relationship Between Physical Activity and Trust in Economic Decision-Making - Laštovková, Petra; Kotrba, Vojtěch; Rotschedl, Jiří, 1982-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2025)
This master's thesis investigates the impact of physical activity on prosocial behavior within the context of economic decision-making, specifically examining trust, trustworthiness, and altruism. Additionally, the thesis analyzes risk-taking behavior. The research employs economic games (trust game, dictator game, and lottery), conducted through a controlled experiment involving women attending recreational Muay Thai classes. Participants were randomly assigned to two groups; one completed the economic games before training, while the other participated immediately following intense physical activity. The results indicate a statistically significant increase in trustworthiness following physical activity. In contrast, trust and altruism exhibited slight but statistically insignificant changes. Risk-taking behavior was unaffected by physical activity. This study contributes valuable insights to behavioral economics, highlighting the potential economic and policy benefits of promoting physical activity as a means to enhance social capital and economic efficiency.
Vedoucí práce: Vojtěch Kotrba
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: ekonomie [obor dipl. práce]; diplomové práce; master's theses